Oocytes could rearrange immunoglobulin production to survive over adverse environmental stimuli - Wang, Yang; Luo, Fu-Qiang; He, Yu-Hao; Yang, Zhi-Xia; Wang, Xin; Li, Cong-Rong; Cai, Bei-Qi; Chen, Liang-Jian; Wang, Zi-Bin; Zhang, Cui-Lian; Guan, Yi-Chun; Zhang, Dong (Frontiers in Immunology, 2022)
Immunoglobulins are key humoral immune molecules produced and secreted by B lymphocytes at various stages of differentiation. No research has reported whether immunoglobulins are present in the non-proliferative female germ cells—oocytes—and whether they are functionally important for oocyte quality, self-protection, and survival. Herein, we found that IgG was present in the oocytes of immunodeficient mice; the IgG-VDJ regions were highly variable between different oocytes, and H3K27Ac bound and regulated the IgG promoter region. Next, IgG mRNA and protein levels increased in response to LPS, and this increment was mediated by CR2 on the oocyte membrane. Finally, we revealed three aspects of the functional relevance of oocyte IgG: first, oocytes could upregulate IgG to counteract the increased ROS level induced by CSF1; second, oocytes could upregulate IgG in response to injected virus ssRNA to maintain mitochondrial integrity; third, upon bacterial infection, oocytes could secrete IgG, subsequently encompassing the bacteria, thus increasing survival compared to somatic cells. This study reveals for the first time that the female germ cells, oocytes, can independently adjust intrinsic IgG production to survive in adverse environments.